Karen and Lawa medicinal plant use: Uniformity or ethnic divergence? - Junsongduang A. (2014)
Ethnopharmacological relevance We here tease apart the ethnopharmacological knowledge of plants in two Thai villages to determine to which degree the uses are particular to individual ethnic groups and to which degree they are part of a generalized and uniform set of widespread medicinal plants used over a large geographic range. We compared Karen and Lawa knowledge of medicinal plants in the Mae Cheam watershed of northern Thailand, where both ethnic groups have settled and share ecological conditions for resource extraction. We were interested in documenting the degree to which these two ethnic groups use the same or different medicinal plant species. The use of the same plant species by the two groups was considered a sign of uniform and cross-cultural local knowledge, whereas the use of different medicinal plants by each group was considered a sign of culturally specific local knowledge that developed within each ethnic group. Materials and methods We inventoried the plant species in different habitats around one Karen village and one Lawa village using stratified vegetation plots and using semi-structured questionnaires we interviewed 67 key informants regarding their use of plants for medicine. We then calculated the Fidelity level FL (FL values near 100% for a species indicate that almost all use reports refer to the same way of using the species, whereas low FL values indicate that a species is used for many different purposes) and cultural importance index CI (the sum of the proportion of informants that mention each of the use categories for a given species) to estimate the variation in medicinal plant use. We used Jaccard's Index JI (This index relates the number of shared species to the total number of species) to analyze the similarity of medicinal plant use between the two villages. Results A total of 103 species of medicinal plant species in 87 genera and 41 families were identified and they were used to cure 35 ailments. The FL of the medicinal plant species varied from 10% to 100%, was different for each ailment, and differed between the two ethnic groups. The most important medicinal plant species, those with the highest CI value, were not the same in the two villages. Costus speciosus, which is used to treat urinary infections and wounds in animals, had the highest CI value in the Karen village, whereas Sambucus javanica, which is used to treat wounds, fractures, bloat, and edema in humans, had the highest CI value in the Lawa village. Only 17 medicinal species (16.5%) were shared between the two villages. Methods of preparation and application were significantly different between the two villages, whereas the plant parts used, habit, and route of administration were similar. Conclusion Our study demonstrates that ethnic groups that live in the same geographic area can have significantly different traditional knowledge systems for medicinal plants, at least when it comes to the species used and their preparation and medicinal application. We assume that differences in cultural history and background in the two villages led to differences in medicinal plant use, preparation, and application. © 2013 Elsevier Ireland Ltd.